2021
DOI: 10.1080/21655979.2021.1982308
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-associated protein 2 like (UBAP2L) enhances growth and metastasis of gastric cancer cells

Abstract: Ubiquitin-proteasome pathway has emerged as therapeutic targets for cancer. GEPIA database analysis showed that the expression of ubiquitin-associated protein 2 like (UBAP2L) in gastric cancer specimens was significantly higher than that in non-tumor tissue, and its high expression is associated with poor survival of gastric cancer patients. This study aims to investigate the role of UBAP2L in gastric cancer. Real-time PCR and western blot results showed that UBAP2L expression was upregulated in gastric cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The membranes were and then incubated with secondary antibodies. The protein bands were visualized using an ECL reagent (GE Healthcare) [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The membranes were and then incubated with secondary antibodies. The protein bands were visualized using an ECL reagent (GE Healthcare) [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Also, we revealed UBAP2L was significantly up-regulated in NSCLC. UBAP2L has been shown to be overexpressed in several tumors, such as liver carcinoma ( Wang et al, 2017 ), breast cancer ( He et al, 2018 ) and gastric cancer ( Lin et al, 2021 ). Also, previous studies showed UBAP2L was amplified in LUAD and is critical for tumor metastasis ( Aucagne et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, in non-small cell lung cancer (NSCLC), miR-19a-3p directly inhibits UBAP2L, resulting in similar phenotypes as those observed upon UBAP2L downregulation, mainly inhibition of cell proliferation, migration and invasion ( Pan et al, 2020 ). Similarly, UBAP2L was silenced by miR-148b-3p in gastric cancer cells leading to the same phenotypes as in NSCLC ( Lin et al, 2021 ). Interestingly, the UBAP2L ortholog PQN-59 stabilizes several miRNAs involved in various cellular functions and interacts with RNA metabolism, transcription and translation cellular components similarly to UBAP2L, highlighting the importance of this protein in RNA regulation ( Carlston et al, 2021 ).…”
Section: Ubap2l and Rnasmentioning
confidence: 95%
“…Consistently, cells lacking UBAP2L harbor increased epithelial (E-cadherin, CK-18) and decreased mesenchymal markers (N-cadherin, vimentin) ( Ye et al, 2017 ), highlighting UBAP2L’s crucial role in regulating the metastatic potential of cancer cells. In addition to HCC, the promotion of EMT by UBAP2L has also been reported in prostate, lung and gastric cancers ( Li and Huang, 2014 ; Aucagne et al, 2017 ; Lin et al, 2021 ). Complementary studies verified these conclusions in vivo where inhibition of UBAP2L led to defective cancer invasion in xenografts ( Guan et al, 2021 ).…”
Section: Ubap2l and Cancermentioning
confidence: 97%
See 1 more Smart Citation